International Undergraduates’ Retention, Graduation, and Time to Degree - Fass-Holmes, Barry (Journal of International Students, 2016)
The present study tested the hypothesis that the international undergraduates at a West Coast American public university during recent years of dramatic enrollment growth should have low retention and graduation rates. This study showed instead that these students were retained and graduated at rates surpassing predictions from research and theories on international undergraduates’ unique challenges (American immigration regulations, academic integrity standards, and teaching methods; English writing) and academic struggles. Moreover, contrary to predictions related to academic struggles, the primary reasons for these students’ attrition were leave of absence for compulsory military service and deciding against attending the University. These results disconfirm the study’s hypothesis and instead suggest that these international undergraduates generally have succeeded academically.